BCG Economy Model: Comparative Study of Thai and Foreign Organizations - Ungskul, Thimpika; Butlang, Natnaree; Dokho, Noorhan; Thongcharoen, Parami; Wan-on, Piravan; Ritthikan, Wipawadi; Noknoi, Chetsada (Journal for Strategy and Enterprise Competitiveness, 2025)
This article aims to provide an understanding of the BCG Economy Model, a concept that applies science, technology, and innovation to enhance sustainable competitiveness. The model includes three components: bioeconomy, circular economy, and green economy, all of which are developed simultaneously. The article begins by explaining the concept and components of the BCG Economy Model, and then compares case studies of two Thai organizations—Café Amazon and Ban Pong Tapioca—and two foreign organizations—Huawei and Amazon. The findings indicate that all organizations conduct their business in line with the BCG Economy Model, covering all three components. However, there remain a significant number of organizations that have not been able to implement the model successfully. Therefore, relevant sectors must cooperate. Executives, in particular, need to understand, promote, support, be aware of, and prioritize sustainable organizational development, while the government should establish standards, laws, tax measures, and related regulations, as well as encourage organizations to improve and develop in order to earn recognition and awards that reflect their commitment to sustainable development.